Rigid polyurethane foams moulded with new generation blowing agents - Prociak, A.; Figura, M. (Polimery, 2022)
Rigid polyurethane foams were moulded with using cyclopentane, HCFC 141b and HFC 365/227 as physical blowing agents. Formulations with various amounts of blowing agents were elaborated and foams showing different density were prepared. The effects of the type and content of blowing agent on the physical, mechanical properties and thermal conductivity of the foams while ageing were investigated. The type of blowing agent affected the profiles of property changes of foams versus density. It has been found that the foams blown with cyclopentane or HFC 365/227 showed, in comparison with those blown with HCFC-141b used up to now, similar or even sometimes better properties.